2015
DOI: 10.1166/jnn.2015.9033
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Hydroxide Activated Nanoporous Carbons Based on Lapsi Seed Stone

Abstract: Nanoporous activated carbons (ACs) were prepared from Lapsi (Choerospondias axillaris) seed powder by chemical activation with sodium hydroxide (NaOH) at different NaOH impregnation ratios. The prepared ACs were characterized by Fourier transform-infrared (FTIR) spectroscopy, Raman scattering, X-ray diffraction (XRD), and scanning electron microscopy (SEM). Semi-quantitative information on the surface properties was obtained by estimating iodine number. FTIR spectra showed the presence of oxygenated functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…It suggested that, all the ACs are amorphous in nature and the graphite crystallite structure of sugarcane bagasse based ACs is not affected by the impregnation ratio (ZnCl 2 /sugarcane bagasse). The result is similar with the X-ray diffraction pattern of NaOH activated Lapsi seed stone [21].…”
Section: Scanning Electron Microscope (Sem)supporting
confidence: 82%
“…It suggested that, all the ACs are amorphous in nature and the graphite crystallite structure of sugarcane bagasse based ACs is not affected by the impregnation ratio (ZnCl 2 /sugarcane bagasse). The result is similar with the X-ray diffraction pattern of NaOH activated Lapsi seed stone [21].…”
Section: Scanning Electron Microscope (Sem)supporting
confidence: 82%
“…Direct carbonization is performed by mild-or high temperature heat-treatment in which pyrolytic decomposition of the precursor occurs with the elimination of many non-carbon elemental species (H, N, O and S), resulting in the formation of fixed carbonaceous char with porous structure. On the other hand, activation processes can be either physical or chemical [10][11][12]. Physical activation includes two-step processes involving carbonization of the precursor material, followed by gasification of the char at elevated temperatures between 800 to 1100 • C using oxidants such as steam, carbon dioxide, air, or the mixture of these gases [13].…”
Section: Introductionmentioning
confidence: 99%
“…The band at 1300-1000 cm -1 may be probably due to the C-O-C lactone structure, the stretching C-O vibrations of phenol structures and ethers, and the bending O-H modes of phenol structures. Similarly, the band at 1700 cm -1 is attributed due to the presence of C=O stretching (Joshi et al, 2014). BET Surface Area BET surface area WAC-Na 2 CO 3 was found to be 10.45m 2 /g, which is considered to be small.…”
Section: Fig 3 Ftir Spectra Of Wac-na 2 Comentioning
confidence: 90%